Mechanical behavior of yttria-stabilized tetragonal zirconia polycrystal: Effects of different aging regimens - Luís Felipe GUILARDI; Gabriel Kalil Rocha PEREIRA; Vinícius Felipe WANDSCHER; Marília Pivetta RIPPE; Luiz Felipe VALANDRO (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This study aimed to characterize and compare the effect of different aging regimens on surface characteristic (topography and roughness), structural stability (phase transformation) and mechanical performance (Weibull analysis) of a Y-TZP ceramic. Discs (15 × 1.2 mm; VITA In-Ceram YZ) were prepared according to ISO 6872-2015 for biaxial flexural strength testing and randomly assigned into five groups (n = 30): as-sintered, no aging treatment (CTRL); 20 h in autoclave at 134°C, 2 bar pressure (AUT); intermittent mechanical loading at 20 Hz/106 load pulses (MechLoad); AUT followed by MechLoad (AUT+MechLoad); and storage in distilled water at 37°C, for 1 year (STO). The following analyses were performed: roughness (n = 30), surface topography (n = 2), phase transformation (n = 2) and biaxial flexure strength (n = 30). Phase transformation (increase of m-phase content) was shown to be a spontaneous, unavoidable and time-dependent process, occurring even under ambient conditions (dry storage after 1 year = 6.0% increase), and is considerably accelerated in the presence of moisture (STO = 17.6%; AUT= 63.1%; and AUT+MechLoad = 59.9%). For roughness parameters, only Ra was affected by aging, and the highest values were observed for AUT+MechLoad (0.25 ± 0.07 µm). For Weibull analysis, structural reliability (Weibull moduli) and characteristic strength were not impaired after aging, and some aging conditions led to increased values (highest weibull moduli in AUT, and highest characteristic strength in STO). Phase transformation proves to be a time-dependent spontaneous mechanism that is accelerated in the presence of different stimuli. However, none of the aging regimens had a negative effect on the characteristic strength and structural reliability of Y-TZP ceramic.